“Desarrollo del sitio web para difusión y el posicionamiento del centro de innovación tecnológica de calzado (CITCA) de la ciudad de Ambato - Sánchez León, David Alejandro (2023)
This Integrating Project analyzed the problems of the global footwear sector, with emphasis on the Ecuadorian context and the Tungurahua region. The impact of CALTU's contribution to the development of footwear in Ecuador through advanced technology and training will be highlighted; but it is necessary to disseminate information from the sector. The objective was to develop a website for the Footwear Technological Innovation Center (CITCA) and disseminate footwear information through digital strategies. The methodology used was the deductive method, with field studies and interviews with experts. The results highlighted the importance of UX/UI design, information architecture, and digital marketing strategies, such as the use of social media management, to increase CITCA 's visibility. In conclusion, a website for ICCTA was developed in conjunction with the media plan for its dissemination